An assessment tool to evaluate complete streets in developing countries: the case of Qatar. (2018) - Shaaban, Khaled; Muley, Deepti; Khalil, Rania
Complete streets refer to a simple and effective transportation policy to improve traffic safety and comfort for all users within urban areas. Car dependency is a major concern in developing countries. Endorsing complete streets in any place could improve the sense of security and make people less dependent on cars. The purpose of this study is to develop a ten-point assessment tool to evaluate the neighbourhoods in developing countries. This tool is capable of identifying strengths and weaknesses areas in any neighbourhood based on the complete streets policy. The tool was developed and tested on a traditional neighbourhood in Qatar. The assessment tool was successful in identifying specific and detailed improvement areas in the case study. This tool can be used in the future to investigate new neighbourhoods during the development phase, redevelop existing neighbourhoods, and improve provisions for modes of transport.